Preparation, characterization and immunological evaluation: canine parvovirus synthetic peptide loaded PLGA nanoparticles - Derman, Serap; Mustafaeva, Zeynep Akdeste; Abamor, Emrah Sefik; Bagirova, Melahat; Allahverdiyev, Adil (BMC, 2015)
Background: Canine parvovirus 2 (CPV-2) remains a significant worldwide canine pathogen and the most common cause of viral enteritis in dogs. The 1 L15 and 7 L15 peptides overlap each other with QPDGGQPAV residues (7-15 of VP2 capsid protein of CPV) is shown to produce high immune response. PLGA nanoparticles were demonstrated to have special properties such as; controlled antigen release, protection from degradation, elimination of booster-dose and enhancing the cellular uptake by antigen presenting cells. Nevertheless, there is no study available in literature, about developing vaccine based on PLGA nanoparticles with adjuvant properties against CPV. Thus, the aim of the present study was to synthesize and characterize high immunogenic W-1 L19 peptide (from the VP2 capsid protein of CPV) loaded PLGA nanoparticle and to evaluate their in vitro immunogenic activity. Results: PLGA nanoparticles were produced with 5.26 +/- 0.05 % loading capacity and high encapsulation efficiency with 81.2 +/- 3.1 %. Additionally, it was evaluated that free NPs and W-1 L19 peptide encapsulated PLGA nanoparticles have Z-ave of 183.9 +/- 12.1 nm, 221.7 +/- 15.8 nm and polydispersity index of 0.107 +/- 0.08, 0.135 +/- 0.12 respectively. It was determined that peptide loaded PLGA nanoparticles were successfully phagocytized by macrophage cells and increased NO production at 2-folds (*P < 0.05) in contrast to free peptide, and 3-folds (*P < 0.01) in contrast to control. Conclusion: In conclusion, for the first time, W-1 L19 peptide loaded PLGA nanoparticles were successfully synthesized and immunogenic properties evaluated. Obtained results showed that PLGA nanoparticles enhanced the capacity of W-1 L19 peptide to induce nitric oxide production in vitro due to its adjuvant properties. Depend on the obtained results, these nanoparticles can be accepted as potential vaccine candidate against Canine Parvovirus. Studies targeting PLGA nanoparticles based delivery system must be maintained in near future in order to develop new and more effective nano-vaccine formulations.
Keywords: Canine Parvovirus; Vaccine; Antigen; Peptide; PLGA; Nanoparticle; Antigen delivery; IMMUNE-RESPONSES; NITRIC-OXIDE; DELIVERY-SYSTEMS; DENDRITIC CELLS; CELLULAR UPTAKE; DRUG-DELIVERY; IN-VITRO; RELEASE; Cell Biology; Research & Experimental Medicine